Analysis of the Influence of Brand Image and Brand Trust on Purchasing Decisions through Brand Loyalty (Study on Lapis Kukus Pahlawan Bread) - purnomo, bambang raditya; dg, indrarini oetoro (Universitas Dr. Soetomo, 2021)
Competition between the food and beverage industry, especially local souvenirs, is a challenge for every business actor to be able to maintain and develop his business. Repurchase decision is the stage where consumers form the intention to buy the most preferred product, where the consumer's decision to modify, delay or avoid is strongly influenced by the perceived purchase risk (Kotler and Keller, 2012: 188).Brand image can influence consumer behavior in buying a product. Brand image has an important position in buying behavior. Because one of the decisions in the purchase structure is a decision regarding the brand. Trust involves a person's willingness to behave in a certain way because of the belief that his partner will give what he hopes and a hope that is generally owned by someone that the words, promises or statements of others can be trusted (Daryanto, 2013: 279).Brand trust is one's belief in certain values that will influence behavior (Peter and Olson, 2013: 136). Brand loyalty reflects brand loyalty to certain brands. Brand loyalty is a condition where consumers have a positive attitude towards the brand, have a commitment to the brand, and have a tendency to continue their purchases in the future.Along with the development of the bread industry in Indonesia, there are also more players in the bread business so that competition in this market is getting tougher. The tight competition in the bread business can be seen from a number of bread business players in Indonesia, including bread with the brand Sari Roti, Lauw, Sharon, BreadTalk, Holland Bakery, and many more including the Lapis Kukus Pahlawan Bread. This study aims to analyze the effect of brand image and brand trust on purchasing decisions of the Lapis Kukus Pahlawan bread through brand loyalty.